2019
DOI: 10.1111/1759-7714.13057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a combination of chemotherapy and immune checkpoint inhibitors and immune checkpoint inhibitors alone for the treatment of advanced and metastatic non‐small cell lung cancer

Abstract: Background Single agent immune checkpoint inhibitors (ICIs) improve survival outcomes compared to chemotherapy for advanced non‐small cell lung cancer (NSCLC), but treatment efficacy widely varies. The combination of ICIs with chemotherapy has shown promising efficacy over chemotherapy alone; however, whether this strategy is superior to single agent ICIs for the treatment of advanced NSCLC remains unknown. Methods The records of 109 patients with advanced NSCLC who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…checkpoint inhibitors improves the treatment efficacy over immune checkpoint inhibitors alone 52 , indicating that combinational approaches would be the future standard treatment in NSCLC 53 . Our results suggested that administration of CCL7 through the intranasal pathway promoted the recruitment of cDC1 into the tumor-burdened lungs and subsequent expansion of CD8 + and CD4 + T cells in the bronchial LNs and tumor-burdened lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…checkpoint inhibitors improves the treatment efficacy over immune checkpoint inhibitors alone 52 , indicating that combinational approaches would be the future standard treatment in NSCLC 53 . Our results suggested that administration of CCL7 through the intranasal pathway promoted the recruitment of cDC1 into the tumor-burdened lungs and subsequent expansion of CD8 + and CD4 + T cells in the bronchial LNs and tumor-burdened lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progresses of several phase III trials have shown that combination of anti-PD-1/PD-L1 immune checkpoint blockades plus chemo-reagents is superior to chemotherapy alone as first-line treatment for advanced NSCLC patients in regard of the OS and PFS 51 . A retrospective study shows that combination of chemotherapy and immune checkpoint inhibitors improves the treatment efficacy over immune checkpoint inhibitors alone 52 , indicating that combinational approaches would be the future standard treatment in NSCLC 53 . Our results suggested that administration of CCL7 through the intranasal pathway promoted the recruitment of cDC1 into the tumor-burdened lungs and subsequent expansion of CD8 + and CD4 + T cells in the bronchial LNs and tumor-burdened lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PD-1/PD-L1 ICIs in combination with chemotherapy may be more effective than anti-PD-1/PD-L1 ICIs alone for the treatment of advanced NSCLC [132]. Therefore, this combination therapy may be suggested as sequential treatment for patients with EGFR-mutant NSCLC who do not have known targetable acquired resistant mutations, but efficacy studies are needed.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, recent studies have found that chemotherapy may have immunomodulatory properties, which can be induced by the tumor microenvironment from the immune desert or immune excluded to a state conducive to the role of immune cells ( 33 ). Even if the proportion of patients with EGFR or ALK mutations increases, chemotherapy may provide some survival benefits ( 34 ).…”
Section: Discussionmentioning
confidence: 99%